Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1302/0301-620x.99b7.bjj-2016-0585.r1
|View full text |Cite
|
Sign up to set email alerts
|

‘Modern’ distal femoral locking plates allow safe, early weight-bearing with a high rate of union and low rate of failure

Abstract: Our study suggests an exponential increase in the incidence of a fracture of the distal femur with age, analogous to the population suffering from a proximal femoral fracture. Allowing immediate unrestricted weight-bearing after LDFLP fixation in these elderly patients was not associated with failure of fixation. There was a high rate of union and low rate of re-operation. Cite this article: 2017;99-B:951-7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 18 publications
0
48
0
3
Order By: Relevance
“…This is often a necessity in periprosthetic fractures where the position of the femoral component may preclude optimal plate positioning. Although a number of studies have shown difficulties in achieving optimal plate fit in locking plate designs, there is as yet no clinical evidence to show any downside to this [7, 36]. As demonstrated in this study however, without bony union, locking plates still have a tendency to fail.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…This is often a necessity in periprosthetic fractures where the position of the femoral component may preclude optimal plate positioning. Although a number of studies have shown difficulties in achieving optimal plate fit in locking plate designs, there is as yet no clinical evidence to show any downside to this [7, 36]. As demonstrated in this study however, without bony union, locking plates still have a tendency to fail.…”
Section: Discussionmentioning
confidence: 64%
“…As the practice of the study location was to make all patients non-weightbearing for a minimum of 6 weeks, analysis was not possible in this regard. Although non-weightbearing is commonly the practice followed in many centres, recent studies [7, 46] have shown successful outcomes including high union rates in patients allowed full weightbearing after locked plating of distal femoral fractures. Although no biomechanical proof currently exists, there may be a beneficial effect on fracture site biology from weightbearing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although various surgical techniques have been described for the unstable PHF, proximal humeral internal locking systems (PHILOS) are increasingly popular for treating these fractures because they offer improved biomechanical properties by providing divergent and convergent fixed‐angle screws that improve fixation and pullout strength in osteoporotic bone. It is also known to be clinically and biomechanically effective in elderly patients with PHF. However, it is difficult to obtain stable fixation in osteoporotic patients even with PHILOS.…”
Section: Introductionmentioning
confidence: 99%
“…Locking plates can provide high fixation stability for fracture healing and good functional recovery in fracture treatment, 1-3 particularly when they are applied using minimally invasive surgical techniques. 4 The advantage of using locking plates is firm screw locking, which can prevent loosening of screws, loss of fracture reduction, and disturbance of bone circulation.…”
Section: Introductionmentioning
confidence: 99%